2013
DOI: 10.1038/ismej.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent niche formation of a pyrite-dependent acidophilic consortium built by archaea and bacteria

Abstract: Biofilms can provide a number of different ecological niches for microorganisms. Here, a multispecies biofilm was studied in which pyrite-oxidizing microbes are the primary producers. Its stability allowed not only detailed fluorescence in situ hybridization (FISH)-based characterization of the microbial population in different areas of the biofilm but also to integrate these results with oxygen and pH microsensor measurements conducted before. The O 2 concentration declined rapidly from the outside to the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 39 publications
0
49
0
Order By: Relevance
“…Heterotrophic metabolisms have been demonstrated for some of the Archaea in enrichments cultures, as well as with pure cultures of ‘ Ferroplasma acidarmanus ’ (Dopson et al ., ; Ziegler et al ., ). Previous work has shown that the Thermoplasmatales come to dominate the community in submerged biofilms (Justice et al ., ), and the increased abundance of Thermoplasmatales protein in Fe 3+ ‐containing environments indicates that Fe 3+ is an important factor in this transition.…”
Section: Discussionmentioning
confidence: 97%
“…Heterotrophic metabolisms have been demonstrated for some of the Archaea in enrichments cultures, as well as with pure cultures of ‘ Ferroplasma acidarmanus ’ (Dopson et al ., ; Ziegler et al ., ). Previous work has shown that the Thermoplasmatales come to dominate the community in submerged biofilms (Justice et al ., ), and the increased abundance of Thermoplasmatales protein in Fe 3+ ‐containing environments indicates that Fe 3+ is an important factor in this transition.…”
Section: Discussionmentioning
confidence: 97%
“…The stimulation of members of the Gammaproteobacteria, Betaproteobacteria, and Alphaproteobacteria, which possess members capable of iron cycling and sulfur oxidation (Baker and Banfield, 2003;Hedrich et al, 2011;Johnson et al, 2012), suggests that precipitate formation within the organic substrate-containing reactors may have occurred over the duration of the field trial possibly limiting OC substrate availability. While anaerobic conditions are necessary for active sulfate reduction and microaerophilic conditions are necessary for iron and sulfur oxidation under low-pH conditions, the concurrence of these two disparate metabolisms may be explained by microniche or biofilm formation within the system (Bertis and Ziebis, 2010;Desai et al, 2013;Ziegler et al, 2013). Future studies will require OC analysis of the reactors as well as further research into the attached versus planktonic microbial community to determine the dynamics occurring within the bioreactors.…”
Section: Mechanisms For Sulfate Removalmentioning
confidence: 99%
“…Because Fe(III) hydroxide minerals schwertmannite and K-jarosite were observed in the river sediment, the Aplasma-related archaeal lineage is inferred to be one of the primary drivers of Fe(II) oxidation in West Dalyup River. These archaeal communities were distinct from those detected in other hypersaline or acidic environments (Baker and Banfield, 2003;Tyson et al, 2004;Ram et al, 2005;Baker et al, 2006;Oren, 2008;Comolli et al, 2009;Andrei et al, 2012;Emmerich et al, 2012;Narasingarao et al, 2012;Yelton et al, 2013;Ziegler et al, 2013;MĂ©ndez-GarcĂ­a et al, 2014).…”
Section: Microbial Community Analysesmentioning
confidence: 99%